The Power - Alderman, Naomi (New York : Little, Brown and Company, 2017)
" Suddenly - tomorrow or the day after - girls find that with a flick of their fingers, they can inflict agonizing pain and even death. With this single twist, the four lives at the heart of Naomi Aldermans extraordinary, visceral novel are utterly transformed, and we look at the world in an entirely new light. What if the power to hurt were in womens hands?"--Goodreads.com
Keywords: Women -- Fiction; Teenage girls -- Fiction; Great powers -- Fiction; Fantasy fiction